Reading colonial Korea through fiction : the ventriloquists - Kim, Chul, 1951- (Critical studies in Korean literature and culture in translation., 2018)
This study examines the roots of modern Korean fiction and its origin in the Japanese colonial period. These essays highlight the intimate connection between modernity and colonialism and provide a wide-ranging investigation into how the language and literature of Korean society was constructed.